2004
DOI: 10.1590/s0004-27492004000600016
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota bacteriana da conjuntiva de doadores de córnea

Abstract: Objetivos: Quantificar e qualificar a microbiota aeróbia da conjuntiva de doadores de córnea segundo a interferência do intervalo de tempo entre o óbito e a colheita do espécime conjuntival, a causa do óbito e a idade do doador e avaliar a atividade biocida de determinados antibióticos aos microrganismos isolados. INTRODUÇÃOA colonização bacteriana da pele, membranas e mucosas, como a conjuntiva, inicia-se logo após o nascimento e não se relaciona apenas à contaminação no canal de parto, mas também aos micror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
0
6
0
5
Order By: Relevance
“…Located in different regions of Brazil, Sorocaba has a population of 500,000 and large economic diversity (16) , in contrast to the city of Rio Branco, which has a population of approximately 350,000 and a barely sustainable economy based on agricultural activities (15) . Despite the fact that the literature shows the possible influence of climate and socioeconomic conditions on conjunctival microbiota (bacterial and fungal) (4,10,(12)(13)(14) , no significant differences were observed in the regions studied with regard to bacterial growth.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Located in different regions of Brazil, Sorocaba has a population of 500,000 and large economic diversity (16) , in contrast to the city of Rio Branco, which has a population of approximately 350,000 and a barely sustainable economy based on agricultural activities (15) . Despite the fact that the literature shows the possible influence of climate and socioeconomic conditions on conjunctival microbiota (bacterial and fungal) (4,10,(12)(13)(14) , no significant differences were observed in the regions studied with regard to bacterial growth.…”
Section: Discussionmentioning
confidence: 66%
“…In the present study, the species of bacteria isolated in the cultures of the conjunctiva of diabetic patients were no different from those identified in the conjunctiva of non-diabetic patients, as was also observed in the study by Martins et al (4) In normal bacterial flora, the aerobic agents most commonly found are Staphylococcus epidermidis, Staphylococcus aureus, Corynebacterium spp and Propionibacterium acne (4,12) . Most studies agree that Staphylococcus epidermidis is the microorganism most commonly found in aerobic bacterial flora of normal conjunctivas (4,10,11,24) . Greater aerobic bacterial growth was also observed in the conjunctivas of the older patients, regardless of gender or the presence or absence of diabetes.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations